Evaluasi Implementasi E-government di Instansi XYZ - Romayah, Siti; Suroso, Arif Imam; Ramadhan, Arief (Universitas Brawijaya, Indonesia, 2014)
Evaluation of e-Government is conducted to improve the efficiency, effectiveness, transparency and accountability of governance and public services. This study aims to evaluate the implementation of e-Government (e-Gov)in XYZ institution. The evaluation is divided into three types, first is analysis of maturity level using e-Gov Ranking Hold Indonesia (PeGI), the second type is evaluation of Information Systems Resources (ISR) with descriptive qualitative method, and the last one is analysis of system quality and information quality based on McLean and DeLone (2003) using analysis of Importance Performance Analysis (IPA). As a result, the overall assessment of PeGI from the five-dimensional measurement is good but it tends to be less threatened either. The dimensions of institutional, infrastructure, and application are categorized as good rank while the dimension of planning and policy are weak rank. Secondly, the evaluation results of ISR including hardware, software, netware, and dataware have good performance but the evaluation results of human resources need to be improved. Furthermore, from the IPA results, the low performance of sistem quality are reliability, accessibility, download time and efficiency and the low performance of information quality are timelines and up-to-date. Accordingly, XYZ institution need to make improvements that focus on information and communication technology (ICT) planning, human resources mapping and improving the quality and quantity in the field of ICT, as well as improving the system quality and the information quality to support the successful implementation of e-Gov in XYZ institution